Influence of negative age stereotypes and anti‐aging needs on older consumers' consumption‐coping behaviours: A qualitative study in South Korea. (8th February 2018) - Bae, Hyeyoon; Jo, Sang Hyun; Han, Semi; Lee, Euehun
Abstract: The number of older people in South Korea is growing dramatically, and the socio‐psychological needs of these people have begun to change from those of elderly people in the previous Confucian culture. The anti‐aging industry is popular among older South Korean consumers, and the Korean mass media have begun to broadcast new images of older people. The purpose of this research was to explore older Korean people's anti‐aging needs by examining their consumption‐related thoughts and behaviours in daily life. A theoretical framework is formulated to organize the coping processes and psychological mechanisms used by older Koreans to meet their anti‐aging needs. A total of 25 older Korean consumers were interviewed, and the qualitative data are analysed to determine the main causes and, attributes of, and reactions to their anti‐aging needs. The analysis of the in‐depth‐interviews shows that the older consumers' negative age stereotypes act as a stressor and that their need for anti‐aging products is a defensive reaction. It is also found that older Korean consumers change their consumption behaviours to cope with negative age stereotypes and to satisfy their anti‐aging needs, and two types of coping behaviours (problem‐focused and emotion‐focused) are revealed. The results of this study contribute to the academic explanations of the anti‐aging phenomenon among older Koreans and enhance understanding of the perspectives of older Eastern consumers by revealing the existence of their anti‐aging needs.